In vitro vasodilator mechanisms of the indole alkaloids rhynchophylline and isorhynchophylline, isolated from the hook of Uncaria rhynchophylla (Miquel) - Zhang, W.B.; Chen, C.X.; Sim, S.M.; Kwan, C.Y. (2004)
Rhynchophylline (Rhy) and isorhynchophylline (Isorhy), indole alkaloids from Uncaria hooks, reportedly exert hypotensive and vasodilatory effects, but the mechanism of action is unclear. We therefore investigated the relaxant effects of these two isomeric alkaloids in rat arteries in vitro, in particular in respect of the various functional Ca2+ pathways. Both Rhy and Isorhy relaxed aortic rings precontracted with phenylephrine (PE, 1 muM) in a dose-dependent manner (3-300 muM). Removal of endothelium and preincubation with L-NAME (300 muM) slightly inhibited but did not prevent the relaxant response. These results indicate that Rhy and Isorhy act largely in an endothelium-independent manner. Unlike nicardipine, both alkaloids not only inhibited the contraction induced by 60 mM KCl (IC50 20-30 muM), but also that induced by PE and U46619, albeit to a lesser extent (IC50 100 and 200 muM, respectively). These results suggest that Rhy and Isorhy may act via multiple Ca2+ pathways. In contrast to their inhibitory effects on KCl-induced and receptor-mediated contractions, where both isomers were comparably potent, Rhy was more potent than Isorhy at higher concentrations (>100 muM) in inhibiting both caffeine (25 mM)- and cyclopiazonic acid (CPA, 30 muM)-induced contractions. Similar results observed with caffeine in Ca2+-containing medium were also observed in Ca2+-free medium. However, 0.1-0.3 muM nicardipine (which completely inhibited KCl-induced contraction) had no significant inhibitory effect on CPA-induced contractions. Taken together, these results indicate discrimination between these two isomers with respect to Ca2+-induced Ca2+ release and non-L-type Ca2+ channel, but not for IP3-induced Ca2+ release and L-type Ca2+ channels. Similar relaxant responses to KCl- and caffeine-induced contractions were seen when these two alkaloids were tested on the smaller mesenteric and renal arteries. In conclusion, the vasodilatory effects of Rhy and Isorhy are largely endothelium independent and are mediated by L-type Ca2+ channels. At higher concentrations, they also affect other Ca2+-handling pathways, although to a lesser extent. While there is no discrimination between the two isomers with respect to the contraction induced by KCl or agonists (PE and U46619), differential effects between Rhy and Isorhy were seen on caffeine- and CPA-induced contractions.